Efektivitas Pembelajaran Geografi Pokok Bahasan Siklus Air Dengan Menggunakan Media Komik Strip Pada Siswa Kelas X Ips Man Purwodadi - Sholiha, Arina; Tukidi, Tukidi; Sriyanto, Sriyanto (Edu Geography, 2017)
The aim of this study was to determine the effectiveness of learning geography subject of the water cycle by using the medium of the comic strip in class X MAN IPS in terms of learning outcomes, level of activity, and student responses. Effectiveness criteria in the study were: (1) the classical mastery learning, (2) the achievement of student activities, and (3) feedback/ studentâs response of the learning. The research design was Pre-Experiment Design with the design of pre-test and post-test group the performed in MAN Purwodadi with the subject of class X IPS 1 totaling 32 students. The result showed that in classical learning completeness reached 81,56%, so the criteria is very effective. Student activity classically reached 75,84% thus qualifies as quite effective, while the studentâs responses to learning falls within the criteria that is 79,8% effective enough. Based on the above results is said to be effective if the three criteria which consists of learning outcomes, student learning activities, and the positive response of studentâs is in conformity with the standard efficacy so that the data the effectiveness of learning by using media comic strip in the classroom X IPS 1 MAN Purwodadi effective enough to very effective. Penelitian ini bertujuan untuk mengetahui tingkat efektivitas pembelajaran geografi pokok bahasan siklus air dengan menggunakan media komik strip pada siswa kelas X IPS MAN dari segi hasil belajar, tingkat aktivitas, dan tanggapan siswa. Kriteria efektivitas dalam penelitian ini adalah: (1) ketuntasan belajar secara klasikal, (2) ketercapaian aktivitas siswa, dan (3) tanggapan/ respon siswa terhadap pembelajaran. Desain penelitian ini adalah Pre-Eksperimental Design dengan rancangan pretest and post-test group yang dilakukan di MAN Purwodadi dengan subjek kelas X IPS 1 yang berjumlah 32 siswa. Hasil penelitian menunjukkan bahwa ketuntasan belajar secara klasikal mencapai 81,56% sehingga pada kriteria ini sangat efektif. Aktivitas belajar siswa secara klasikal mencapai 75,84% sehingga masuk dalam kriteria cukup efektif, sedangkan tanggapan siswa terhadap pembelajaran masuk dalam kriteria cukup efektif yaitu 79,8%. Berdasarkan hasil penelitian di atas dikatakan efektif apabila ketiga kriteria yang terdiri dari hasil belajar, aktivitas belajar siswa, dan respon positif siswa sudah sesuai dengan standart efektivitas sehingga data efektivitas pembelajaran dengan menggunakan media komik strip dalam pembelajaran di kelas X IPS 1 MAN Purwodadi cukup efektif hingga sangat efektif.